2016
DOI: 10.1021/acs.orglett.6b01832
|View full text |Cite
|
Sign up to set email alerts
|

An Iminium Salt Organocatalyst for Selective Aliphatic C–H Hydroxylation

Abstract: The first examples of catalysis of aliphatic C-H hydroxylation by an iminium salt are presented. The method allows the selective organocatalytic hydroxylation of unactivated 3° C-H bonds at room temperature using hydrogen peroxide as the terminal oxidant. Hydroxylation of an unactivated 2° C-H bond is also demonstrated. Furthermore, improved functional group compatibility over other catalytic methods is reported in the form of selectivity for aliphatic C-H hydroxylation over alcohol oxidation. On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…[50] This observation supports the hypothesis that this reaction also proceeds through aHAT mechanism. [50] This observation supports the hypothesis that this reaction also proceeds through aHAT mechanism.…”
Section: Angewandte Chemiesupporting
confidence: 77%
See 1 more Smart Citation
“…[50] This observation supports the hypothesis that this reaction also proceeds through aHAT mechanism. [50] This observation supports the hypothesis that this reaction also proceeds through aHAT mechanism.…”
Section: Angewandte Chemiesupporting
confidence: 77%
“…A similar selectivity pattern (yields of 45 % and 9 % in cyclohexanol and cyclohexanone, respectively) was observed when the oxidation of cyclohexane was carried out in HFIP in the presence of H 2 O 2 and the iminium salt catalyst A , a precursor of an oxaziridinium species . This observation supports the hypothesis that this reaction also proceeds through a HAT mechanism.…”
Section: C−h Bond Deactivationmentioning
confidence: 99%
“…Based on the above results, the PIDA is likely to be the source of oxygen. To further verify the essential role of PIDA in the reaction, some other oxidants such as hydrogen peroxide, m ‐CPBA, t BuOOH, Ag 2 O and CuO were utilized under the same reaction conditions as those in Entry 1 (Entry 3–7), failed to obtain any desired product. The results showed that replacement of PIDA with some other hypervalent iodine compounds such as phenyliodine bistrifluoroacetate (PIFA), Dess Martin periodinane (DMP), only PIFA could carry the reaction well and improve the yield (Entry 8–9).…”
Section: Resultsmentioning
confidence: 99%
“…Im Vergleich dazu wurde bei der Oxidation von Cyclohexan in HFIP unter Verwendung von H 2 O 2 und Iminiumsalzkatalysator A , einer Vorstufe einer Oxaziridiniumspezies, ein ähnliches Selektivitätsmuster (45 % und 9 % Ausbeute an Cyclohexanol bzw. Cyclohexanon) beobachtet, was die Annahme bestärkt, dass auch diese Reaktion über einen HAT‐Mechanismus verläuft.…”
Section: C‐h‐bindungsdeaktivierungunclassified